Irrigating Solutions and Activation Methods Used in Clinical Endodontics: A Systematic Review - Tonini, Riccardo; Salvadori, Matteo; Audino, Elisabetta; Sauro, Salvatore; Garo, Maria Luisa; Salgarello, Stefano (Frontiers in Oral Health, 2022)
Background Ex vivo and in vitro studies have demonstrated the effectiveness of some irrigation protocols in reducing the bacterial load in the root canal system. However, standardized protocols have not yet been defined for the real clinical context due to many irrigation procedures available. Objective To evaluate the clinical endodontic protocols and limitations of irrigating solutions in the disinfection of the root canal system in patients with apical periodontitis. Methods PubMed, Scopus, Embase, Web of Science, and Cochrane databases were searched for randomized controlled trials (RCT) published until January 2021. Hand searching was also performed. Studies focused on evaluating the effectiveness of irrigating solutions and/or irrigation activation methods in reducing the bacterial load in the root canal system were considered. The Cochrane risk-of-bias tool for randomized trials (RoB2) was used to assess the quality of the studies. Results Four hundred and twenty eight published articles were identified. After removing the duplicate studies and analyzing full texts, seven RCTs were selected. Two studies compared pure NaOCl with some combination of NaOCl with HEDP and MTAD. Two studies analyzed the antibacterial efficacy of NaOCl and chlorhexidine (CHX). Three studies compared conventional needle irrigation with different irrigation activation methods (PUI, XP-endo finisher, F-file activator, EndoVac activator). The review attained a satisfactory methodology. The main results of each included study were described. Discussion Activation methods provide significantly higher biofilm reduction than conventional needle irrigation methods. Combinations of NaOCl with different chelating agents were ineffective in terms of antimicrobial, but it could potentially increase the risk of irrigant extrusion. However, the irrigating protocols were not carefully detailed, especially those regarding the irrigants application time or total volume. The existing literature lacks high-quality studies. The level of evidence is moderate. Conclusions The available data is too heterogeneous to compare and identify the superiority of specific valuable irrigation protocols in each clinical context. Application time, volume, and activation methods should be standardized to determine the optimal irrigating procedures to reduce the bacterial load and ensure higher predictability of the endodontic treatment. Systematic Review Registration (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=218555), PROSPERO registration: CRD42020218555.